“Faith Comes and Removes All Questions. Faith Helps Me a Lot”: The Unique Perspective of Mothers of Children With Intellectual and Developmental Disabilities in the Ultra-Orthodox Society - Zriker, Amit; Freund, Anat; Erlich, Reizy; Shoker, Yishay (2024)
The collectivist way of life of the ultra-Orthodox society highlights the process of caring for family members with various disabilities. However, little is known about this process in the context of caring for children with intellectual and developmental disabilities. By performing semi-structured interviews with 15 mothers of children with IDD in the ultra-Orthodox society, three main themes emerged: Relationship with the nuclear and extended family; Relationship with the community; Religion and belief. Considering the rise in awareness of the need for professional and formal caring, it is highly important to develop a tailored policy that will include culturally sensitive interventions.
Keywords: ultra-orthodox Jewish; Phenomenological Research; intellectual-developmental disabilities; Faith-based communities; Culturally-sensitive policy